A case study on dome structure of composite structural insulation panels with ANSYS simulations - Liang, Chunhang; Zhu, Liming (Frontiers in Materials, 2022)
Dome structures are conventionally built with concrete. However, the building process is time-consuming and of high labor cost. Composite Structural Insulation Panels(CSIPs) has recently been regarded to be suitable for large-span civil structures, in terms of its light weight, easy processing, and mass production. Hence, this paper explores the practical feasibility of CSIPs domes applied in large-span dome structures by comparing the performance of CSIPs domes with conventional thin-shell concrete domes in terms of stiffness, strength, and stability by means of refined finite element analysis. Results demonstrate CSIPs dome possesses good dynamic performance, bears larger nonlinear flexure loads, and even copes with stress loads under earthquakes. Moreover, the stiffness should be handled in the onsite applications to fulfil the safety requirement.